The Pedagogical Residence Program and its contributions to the teacher training of the Rural Education course, Abaetetuba, Pará - Ieda Ribeiro Rodrigues; Graciete do Socorro do Nascimento da Silva; Clemerson Santos da Silva; Ronaldo Lopes de Sousa; Marcio Antonio Raiol dos Santos (Universidade Federal do Norte do Tocantins, 2021)
The Pedagogical Residency Program (PRP) is an action implemented by Capes to meet the objectives of the National Policy for the Training of Teachers of Basic Education of the Ministry of Education. Based on the need to systematize the residents' evaluation of the program to have the perception that the licensee is favored after living with their future reality while preparing for the profession, the objective is to present the results that the Pedagogical Residency Program provided for the academic training of students of the 2015 course in Education of the Class countryside, Federal University of Pará (UFPA), Abaetetuba Campus/Pará. It is based on the historical process of the program, emphasizing the Rural Education subproject. Since, through a qualitative approach, semi-structured questionnaires were applied via WhatsApp and E-mail, for 26 (twenty-six) residents and for the 3 (three) preceptors of the Rural Education subproject. The actions developed by the PRP provided UFPA with the basic school, the search for alternative methodologies by residents and preceptors as a way of providing better learning conditions for the students contemplated by the project. In addition, it contributed to the professional reaffirmation, improved self-esteem and made it possible for the students included in the PRP to experience the reality of rural and city schools. In this way, the activities developed by the PRP went through academic training and allowed participants to experience many collective experiences in the school and UFPA environment, making them more accessible to realize how much the exchange of knowledge can make learning more dynamic and accessible in schools brazilian basic.